Analysis Of Microbiological Quality in Community-Based SPAM (Drinking Water Supply Systems) in The City Of Blitar Based On A Monitoring System - Yuniana Amalia Hayati; Ukik Agustina (Universitas STRADA Indonesia, 2024)
Water is a natural resource that has a very important function for human life. The aim of this research is to analyze the effect of monitoring on the microbiological quality of community-based SPAM (Drinking Water Supply System) in Blitar City. The design of this research is quantitative observational research with a cross sectional approach with the focus of the research directed at analyzing the effect of supervision on microbiological quality in community-based SPAM (Drinking Water Supply Systems) in Blitar City. The total population was 22 respondents and the sample was 21 respondents taken using the Simple Random Sampling technique. The findings showed that the majority of respondents had less supervision in the category of 18 respondents (86%). Apart from that, the majority of community-based SPAM (drinking water supply systems) have microbiological quality in the category of not meeting the requirements, as many as 18 respondents (86%). Based on the results of the Logistic Regression analysis, it shows that the p-value is 0.000 < 0.05, so H1 is accepted so it is concluded that there is an influence of supervision on the microbiological quality of community-based SPAM (Drinking Water Supply System) in Blitar City. It is hoped that respondents will improve supervision to be even better in accordance with applicable regulations in order to ensure the quality of existing SPAM drinking water is suitable for consumption.